2019
DOI: 10.1038/s41598-019-51809-2
|View full text |Cite
|
Sign up to set email alerts
|

A MultiTEP platform-based epitope vaccine targeting the phosphatase activating domain (PAD) of tau: therapeutic efficacy in PS19 mice

Abstract: Pathological tau correlates well with cognitive impairments in Alzheimer’s disease (AD) patients and therefore represents a promising target for immunotherapy. Targeting an appropriate B cell epitope in pathological tau could in theory produce an effective reduction of pathology without disrupting the function of normal native tau. Recent data demonstrate that the N-terminal region of tau (aa 2-18), termed the “phosphatase activation domain (PAD)”, is hidden within native Tau in a ‘paperclip’-like conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 76 publications
(81 reference statements)
2
29
0
Order By: Relevance
“…Intriguingly, PS19 mice also display a small reduction in resting neocortical and hippocampal CBF at 2–3 months of age [ 20 ]. Moreover, it has been shown in different studies that these mice display age-related behavioural alterations at various ages from 3 to 12 months [ 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For the first time, we systematically and cumulatively assessed behavioural function, resting neocortical CBF and tau pathology in PS19 mice at the age points of 2, 4, 6, 8 and 12 months in a single study under one experimental condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, PS19 mice also display a small reduction in resting neocortical and hippocampal CBF at 2–3 months of age [ 20 ]. Moreover, it has been shown in different studies that these mice display age-related behavioural alterations at various ages from 3 to 12 months [ 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For the first time, we systematically and cumulatively assessed behavioural function, resting neocortical CBF and tau pathology in PS19 mice at the age points of 2, 4, 6, 8 and 12 months in a single study under one experimental condition.…”
Section: Discussionmentioning
confidence: 99%
“…PS19 mice also show impaired contextual memory at 6 months [ 10 ] and reduced nociceptive thresholds and altered motor coordination at 9 and 10 months of age [ 4 ]. Moreover, these tau mice display impaired spatial learning and memory and object recognition memory at 8–9 months [ 11 , 15 , 16 ], although Sun et al reported no significant behavioural deficits in the water maze at 9 and 12 months of age [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the N-terminal region tau (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), also known as phosphatase activating domain (PAD), has been appropriately formulated and used for vaccinating transgenic mice, since PAD becomes exposed in pathological tau and plays an essential role in tau polymerization. [34,78,91,92]. The N-terminal region of tau is also the target of many passive anti-tau immunotherapies [11,93].…”
Section: Peptide Epitopes Used In Tau-vaccinesmentioning
confidence: 99%
“…To this end, a series of animal models for AD or other neurodegenerative diseases have been created/selected and used. Focusing on studies recently reported, various transgenic mouse models including APP/PS1 [71,77]/APPswe/PS1dE9 co-expressing human APP with Swedish mutation and exon-9-deleted presenilin [72,76,95], TauP301S of AD and Frontotemporal dementia phenotype [40,94,97], 3xTg-AD involving both Aβ and p-tau pathology [70,80,82,83,100], EAE/AD deriving from APP/PS1 crossed with EAE (experimental autoimmune encephalomyelitis) [84], Tau22/5xFAD developing both pathological Aβ and tau aggregates [78], PS19 [92], J20 [81], SNCA-OVX [43], B6SJL [111], Tg2576 as well as Tg-SwDI [79], and Tg4510 [34,96] have been employed. On the other hand, a few studies have employed Balb/C or C57/BL6 mice, so as to preliminarily estimate the vaccine capability of eliciting high antibody titers [73][74][75] (Table 2).…”
Section: Animal Models and Immunization Schemes Used In Recent Preclinical Studiesmentioning
confidence: 99%
“…The Alzheimer's disease (AD) vaccine candidate AV-1980R/A elicited high antibody responses, reduced the levels of insoluble tau protein, and improved both motor and cognitive functions in a mouse model of AD. 8 The vaccine targets the N-terminal domain of the tau protein, which is exposed in misfolded version of tau typical in AD, but hidden in native conformation. AV-1980R/A, a recombinant vaccine administered with Advax CpG adjuvant, combines the targeted peptide with several viral and bacterial antigens.…”
Section: Tau Vaccine Ameliorated Alzheimer's Disease In Micementioning
confidence: 99%